Pengaruh LDR, NPL, CAR dan DPK terhadap ROA pada Perusahaan Perbankan Periode 2015-2019 - Shri Aswini; Erika Gunawan; Kevin Chaniago; Fuji Astuty (Politeknik Ganesha Medan, 2021)
This slowing economy resulted in disrupted banking activities, especially profits decreased. The purpose of this study was to determine the effect of the Loanito Deposit Ratio, Non Performing Loans, Capital Adequacy Ratio, and third Party Funds on Returning Assets in Banking Companies on the Indonesia Stock Exchange 2015-2019 Period either partially or simultaneously. This research approach is quantitative. This type of research is descriptive statistics. The nature of this research is explanatory research. The population in this study was 45 banking companies in the Indonesia Stock Exchange for the 2015-2019 period. Technique sampling for this research used purposive sampling. So this research sample was 23 banking companies. Multiple linear regression model. The result is that the Loan to Deposit Ratio has no effect on Returning Assets in Banking Companies on the Indonesia Stock Exchange for the 2015-2019 Period. Non-Performing Loans have a negative effection Return on Assets in Banking Companies on the Indonesia Stock Exchange for the 2015-2019 Period. Capital Adequacy Ratioihas a positive effect on Return on Assets in Banking Companies the Indonesia Stock Exchange 2015-2019 Period. ThirdParty Funds have no effect on return on assets in Banking Companies on the Indonesia Stock Exchange for the 2015-2019 Period. Together Loan to Deposit Ratio, Non-Performing Loans, Capital Adequacy Ratio, and Third Party Funds have an effect on return on assets in Banking Companies the Indonesia StockiExchange 2015-2019 Period. The magnitude of this influence is 25.4% where the remaining 74.6% is influenced by other independent variables for example the ratio of income to operating expenses